Search for Invisible Decays of Sub-GeV Dark Photons in Missing-Energy Events at the CERN SPS; Physical Review Letters; Vol. 118, iss. 1 - Banerjee D.; Burtsev V. E. Vitaly Evgenjevich; Cooke D.; Crivelli P.; Depero E.; Dermenev A. V.; Donskov S. V.; Dubinin F.; Dusaev R. R. Renat Ramilyevich; Emmenegger S.; Fabich A.; Frolov V. N.; et al. (2017, 2017)
Title screen